2015
DOI: 10.5365/wpsar.2015.6.2.004
|View full text |Cite
|
Sign up to set email alerts
|

Non-tuberculous mycobacteria: baseline data from three sites in Papua New Guinea, 2010–2012

Abstract: Objective: To determine the proportion of non-tuberculous mycobacteria (NTM) in samples of pulmonary tuberculosis (TB) cases from Papua New Guinea who were diagnosed using acid-fast microscopy. Methods:As part of a case detection study for TB, conducted in three provincial hospitals in Papua New Guinea, sputum samples of suspected tuberculous cases aged 15 years or older were collected from November 2010 to July 2012. Mycobacterial species isolated from sputum and grown in culture were examined to distinguish … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 26 publications
0
8
0
Order By: Relevance
“…NTM can be isolated from culture. The prevalence of NTM infection has increased in low-TB burden countries, and NTM is frequently isolated from TB suspects even in high-TB burden countries [ 23 24 ]. NAATs are useful for differentiating between MTB and NTM in smear-positive samples [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…NTM can be isolated from culture. The prevalence of NTM infection has increased in low-TB burden countries, and NTM is frequently isolated from TB suspects even in high-TB burden countries [ 23 24 ]. NAATs are useful for differentiating between MTB and NTM in smear-positive samples [ 16 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that among the drug resistance TB cases in treatment failures attending the TB Clinics are suspected to have NTM infections (Ley et al . ; Riello et al . ).…”
Section: Discussionmentioning
confidence: 99%
“…The NTMs are often resistant to antibiotics and anti-tuberculosis treatment (ATT); such patients are quite often misdiagnosed as DR-TB when they fail to respond to regular ATT. Studies have shown that among the drug resistance TB cases in treatment failures attending the TB Clinics are suspected to have NTM infections (Ley et al 2015;Riello et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Samples with duplicate reactivity of the IS 6110 assay as well as reactivity of the senX3-regX3 assay were considered MTB-positive, while samples with duplicate reactivity of the IS 6110 assay only were classified as MTBC/NTM. In PNG, only a small number of NTM strains have been identified, and they are likely to have limited influence in the context of our study [4,26,31]. However, because the possibility of rare NTM in the IS 6110 -positive samples cannot be completely excluded, we have used the ‘MTBC/NTM’ classification for accuracy.…”
Section: Study Population and Methodsmentioning
confidence: 99%